Assessing decisional transparency in local public administration - Ranta, Ana Elena (Central European Public Administration Review, 2026)
Purpose: This study examines the extent to which rural local public authorities in the North-West region of Romania comply with legal obligations concerning decisional transparency and citizen engagement in the adoption of normative acts during the period 2021–2023. It also explores patterns of public participation and institutional communication within the local decision-making process. Design/Methodology/Approach: The research adopts a quantitative approach based on the analysis of transparency reports published online by local public authorities, as required under national legislation. The dataset comprises 403 communes, of which 143 made accessible reports available. The study assesses trends in compliance, the frequency of draft normative acts, communication practices, and indicators of citizen participation, such as attendance at public meetings and requests for information. Findings: The findings reveal a persistent shortfall in compliance with reporting obligations, with only 12.72% of communes publishing reports in 2021, 15.21% in 2022, and 7.98% in 2023. Citizen participation remains limited and uneven, with more visible engagement observed in Bistri?a-Năsăud and Sălaj counties. Despite a rise over time in the number of draft normative acts, the number of public announcements declined. Participation in public meetings reached its highest level in 2022, before decreasing substantially in 2023. Moreover, the very low number of information requests submitted by citizens and business associationssuggests either limited public awareness of, or limited interest in, the decision-making process. Practical Implications: The findings point to the need for stronger institutional efforts to improve compliance with transparency regulations, enhance digital accessibility, and diversify communication strategies. They also underline the importance of raising public awareness and fostering civic partnerships in order to strengthen citizen engagement and ensure more inclusive local governance. Originality/Value: This study provides a timely empirical assessment of transparency practices in rural Romania, thereby contributing to the literature on local governance and participatory democracy in post-transition contexts. By focusing on a large sample of communes over a recent three-year period, it highlights structural limitations in administrative capacity and citizen-state interaction, while also offering a foundation for future research and policy development.
Keywords: decision making; Law 52/2003; odločanje; podeželje; rural; transparency; transparentnost; Zakon 52/2003